Study on a quadratic Hadamard type fractional integral equation on an unbounded interval - Wang, JinRong; Zhu, Chun; Zhou, Yong (Topological Methods in Nonlinear Analysis, 2013)
In this paper, a quadratic Hadamard type fractional integralequations on an unbounded interval is studied. By applying atechnique of measure of noncompactness and Schauder fixed pointtheorem, existence and uniform local attractivity of solutions arepresented after overcoming some difficulty from the Hadamard typesingular kernel. Moreover, three new solutions sets who tend to zeroat infinity are constructed to obtain local stability of solutions.Finally, two examples are made to illustrate our theory results.